Strapped for Cash: The Role of Financial Constraints for Innovating Firms - Esther Ann Bøler; Andreas Moxnes; Karen Helene Ulltveit-Moe (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper makes use of a reform that allowed firms to use patents as stand-alone collateral, to estimate the magnitude of collateral constraints and to quantify the aggregate impact of these constraints on misallocation and productivity. Using matched firm-bank data for Norway, we find that bank borrowing increased for firms affected by the reform relative to the control group. We also find an increase in the capital stock, employment and innovation as well as equity funding. We interpret the results through the lens of a model of monopolistic competition with potentially collateral constrained heterogeneous firms. Parameterizing the model using well-identified moments from the reduced form exercise, we find quantitatively large gains in output per worker in the sectors in the economy dominated by constrained (and intangible-intensive) firms. The gains are primarily driven by capital deepening, whereas within-industry misallocation plays a smaller role.
Keywords: D25; G32; L25; L26; O34; O47; 330; intangible capital; patents; credit constraints; misallocation; productivity